Design, synthesis and biological evaluation of chalcone analogues with novel dual antioxidant mechanisms as potential anti-ischemic stroke agents - Jiabing Wang; Lili Huang; Chanchan Cheng; Ge Li; Jingwen Xie; Mengya Shen; Qian Chen; Wulan Li; Wenfei He; Peihong Qiu; Jianzhang Wu (Elsevier, 2019)
Scavenging reactive oxygen species (ROS) by antioxidants is the important therapy to cerebral ischemia-reperfusion injury (CIRI) in stroke. The antioxidant with novel dual-antioxidant mechanism of directly scavenging ROS and indirectly through antioxidant pathway activation may be a promising CIRI therapeutic strategy. In our study, a series of chalcone analogues were designed and synthesized, and multiple potential chalcone analogues with dual antioxidant mechanisms were screened. Among these compounds, the most active 33 not only conferred cytoprotection of H2O2-induced oxidative damage in PC12 cells through scavenging free radicals directly and activating NRF2/ARE antioxidant pathway at the same time, but also played an important role against ischemia/reperfusion-related brain injury in animals. More importantly, in comparison with mono-antioxidant mechanism compounds, 33 exhibited higher cytoprotective and neuroprotective potential in vitro and in vivo. Overall, our findings showed compound 33 could emerge as a promising anti-ischemic stroke drug candidate and provided novel dual-antioxidant mechanism strategies and concepts for oxidative stress-related diseases treatment. KEY WORDS: Reactive oxygen species, Cerebral ischemia-reperfusion injury, Stroke, Dual-antioxidant mechanism, Chalcones, Antioxidants, Oxidative stress, NRF2/ARE